(untitled) (Sociología y tecnociencia, 2026)
The social implications of biotechnological change in rural communities are an underexplored topic in sociology. The objective of this study was to conduct a systematic review of the literature in Scopus, Web of Science, and ProQuest between 1975 and 2020. The study consisted of two parts. The first identified the state of the art, limited to 52 scientific articles, of which 10 were selected for further study. The second part answers questions about current trends. The findings indicate that research trends are: political economy, social media discourse, social capital networks, patents, and the "neoliberal diet."